2017
DOI: 10.13031/jash.11563
|View full text |Cite
|
Sign up to set email alerts
|

Operator Exposure to Hydrogen Sulfide from Dairy Manure Storages Containing Gypsum Bedding

Abstract: Dairy manure storages containing gypsum-based bedding have been linked anecdotally with injury and death due to presumed dangerous levels of gases released. Recycled gypsum products are used as a cost-effective bedding alternative to improve animal welfare and provide agronomic benefits to manure recycled back to the land. Sulfur contained in gypsum (calcium sulfate) can contribute to hydrogen sulfide (H2S) gas formation under the anaerobic storage conditions typical of dairy manure slurry. Disturbance of stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Inorganic materials have been shown to be unsuitable for use in CBP because they do not promote composting (Galama et al, 2011). Gypsum from wallboard produces hydrogen sulfide under anaerobic conditions and consequently can have health effects on operators during removal of the anaerobic layer during cleanout (Fabian-Wheeler et al, 2017). An active microbial aerobic compost layer can act as a biofilter throughout the year to oxidize the hydrogen sulfide gases diffusing from the anaerobic layer.…”
Section: Bedding Materialsmentioning
confidence: 99%
“…Inorganic materials have been shown to be unsuitable for use in CBP because they do not promote composting (Galama et al, 2011). Gypsum from wallboard produces hydrogen sulfide under anaerobic conditions and consequently can have health effects on operators during removal of the anaerobic layer during cleanout (Fabian-Wheeler et al, 2017). An active microbial aerobic compost layer can act as a biofilter throughout the year to oxidize the hydrogen sulfide gases diffusing from the anaerobic layer.…”
Section: Bedding Materialsmentioning
confidence: 99%
“…These experiments revealed that the fluorescence response after 5 min of exposure to an atmosphere containing 11 ppm H 2 S is distinctly higher compared to a reference sample which was exposed to synthetic air for 30 min. 11 ppm H 2 S is a concentration that for instance workers involved in manure storage or handling on farms are frequently exposed to (Fabian-Wheeler et al, 2017). For the hydrogel film format used here, we determined that approximately 1 h is needed to achieve complete saturation of the system.…”
Section: Resultsmentioning
confidence: 99%
“…At low concentrations (0.01-0.3 ppm v ) H 2 S produces foul smells and the effects of H 2 S on human health at different concentrations are summarized in Table 1. Thus, the maximum exposure concentration permitted in the industry is 10 ppm v , with peaks of 50 ppm v accepted for a duration of 10 min [4,5]. Table 1.…”
Section: Introductionmentioning
confidence: 99%